Water Scarcity in the Mediterranean Perspectives Under Global Change - Sabater, Sergi.; Sabater, Sergi.; Barceló, Damià.; Barceló, Damià. (The Handbook of Environmental Chemistry, 2010)
Water scarcity affects hydrologic resources, systems connectivity, biodiversity, water quality, and river ecosystem functioning. It has direct impacts on economic sectors that use and depend on water, such as agriculture, tourism, industry, energy and transport. The Mediterranean Basin is one of the regions in the world most vulnerable to climate changes, as well as one of the most impacted by human water demand. This volume provides an in-depth view of the water quality and quantity implications of water scarcity. It highlights its possible causes and describes the effects in regions under Mediterranean climate. The topics covered include climate effects, water resources (use, storage and new sources), water quality (chemical and microbiological), and the effects on ecosystems suffering from water scarcity. This book is addressed to scientists and students, but also to managers involved in the necessary decision making process to face future periods of drought.